2013
DOI: 10.1073/pnas.1308887110
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of macrophage phenotype by cell shape

Abstract: Phenotypic polarization of macrophages is regulated by a milieu of cues in the local tissue microenvironment. Although much is known about how soluble factors influence macrophage polarization, relatively little is known about how physical cues present in the extracellular environment might modulate proinflammatory (M1) vs. prohealing (M2) activation. Specifically, the role of cell shape has not been explored, even though it has been observed that macrophages adopt different geometries in vivo. We and others o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

95
1,011
10
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,156 publications
(1,118 citation statements)
references
References 34 publications
95
1,011
10
2
Order By: Relevance
“…This result suggested a possible defect in the migration capabilities of the Pik3ca MUT/-macrophages, with elongated macrophage morphologies recently being associated with a tumor-promoting M2 phenotype (47). Our finding that these macrophages accumulated in the periphery and that the number of infiltrating cells in the tumor was clearly lower further supports the concept of a migration defect.…”
Section: Discussionsupporting
confidence: 72%
“…This result suggested a possible defect in the migration capabilities of the Pik3ca MUT/-macrophages, with elongated macrophage morphologies recently being associated with a tumor-promoting M2 phenotype (47). Our finding that these macrophages accumulated in the periphery and that the number of infiltrating cells in the tumor was clearly lower further supports the concept of a migration defect.…”
Section: Discussionsupporting
confidence: 72%
“…Previous studies using poly(L-lactide) [45] or poly(1-caprolactone) [46] demonstrated that the concentration of pro-inflammatory molecules is lower in cultures in contact with electrospun fibrous surfaces than in cells on solvent-cast films. A surface topography that induces macrophage elongation was found to favour macrophage polarization into an anti-inflammatory phenotype, and, although the mechanisms are still not fully described, it was suggested that polarization via topographic signalling is mediated by actin cytoskeleton contractility [47]. The differences found in this study on microglia behaviour highlight the need for studying microglia in detail.…”
Section: Discussionmentioning
confidence: 65%
“…M1 and M2 macrophages are known to exhibit distinct shapes (i.e., M1 macrophages are round; M2 macrophages are elongated) (36). Our results showed that mouse bone marrow-derived macrophages treated with DMEM or ED-Siglec-9 were spherical, whereas those treated with SHED-CM or ED-Siglec-9/MCP-1 were elongated and expressed a high level of CD206 (Supplemental Fig.…”
Section: Mcp-1 and Ed-siglec-9 Synergistically Induce M2 Macrophagesmentioning
confidence: 60%